Health workforce in India: opportunities and challenges - Nair, Kesavan Sreekantan (International Journal Of Community Medicine And Public Health, 2019)
Health system reforms in India during the past decade yielded an impressive growth of medical, dental and nursing education opportunities, but health workforce density remains low in comparison to the World Health Organization (WHO) norms. Apart from shortage, retaining qualified health workforce in the rural and underserved areas remains a huge challenge. This crisis is likely to persist until and unless health system addresses the fundamental requirements of health workers as envisaged in health policies. Concerted attention and long term political commitments are required to overcome health system barriers to achieve rural recruitment and retention across various cadres in states. As the major share of health workforce belongs to the private sector, their resources need to be harnessed to meet health system goals through partnerships and collaborations. There is an urgent need for better regulation and enforcement of standards in medical education and delivery of health services across the public and private sectors.